Bridging Collective Memories and Public Agendas: Toward a Theory of Mediated Prospective Memory. (19th March 2013) - Tenenboim‐Weinblatt, Keren
Abstract : While memory can be both retrospective and prospective, referring to either what happened or what needs to be done, scholarship on media and collective memory has focused on retrospective memories. Shifting the focus to the news media as agents of prospective memory, this article develops the notion of mediated prospective memory. This new construct, which encompasses the various media practices by which collective prospective‐memory tasks are shaped and negotiated, is intended to shed light on one facet of the complex relationships between past, present, and future in news discourse; create a much needed bridge between the theoretical frameworks of agenda setting and collective memory; and provide one possible answer to the question of what is unique about journalism's memory work .